Visual information in basketball jump-shots: differences between youth and adult athletes - Marques, R.; Martins, F. M. L.; Gomes, R.; Martinho, D. V.; Mendes, R.; Moore, S. A.; Dias, G., Coelho-e-Silva, M. J. (Journal of Human Kinetics, 2023)
Basketball shooting is a complex skill that requires visual routines and trained players typically evidence a specific oculomotor pattern. This study aimed to examine visual patterns in male novice youth and professional adult players while performing a jump shot. The sample included 20 basketball players grouped as under-16 youth (n = 10) and professional adult (n = 10) players. Each participant completed 50 shots at two distances (long range: 6.80 m; middle range: 4.23 m). Eye tracking glasses were used to obtain quiet eye (QE), the number of fixations, total fixation duration, duration of first and last fixation. An independent t-test was used to assess differences between groups. Shooting accuracy given by % of efficacy indicated that under-16 players attained poorer scores at both distances: long (t = -4.75, p < 0.01) and middle (t = -2.80, p < 0.012) distance. The groups also differed in QE time (long: 600 ms vs. 551 ms; middle: 572 ms vs. 504 ms) and total duration of the fixations (long: 663 ms vs. 606 ms; middle: 663 ms vs. 564 ms) in both long and middle distance shots. Significant differences also occurred in the last fixation (long distance: t = -4.301, p < 0.01; middle distance: t = -3.656, p < 0.01) with professional adult players presenting the value of, on average, 454-458 ms, while youth shooters 363-372 ms. In summary, visual strategy differed between under-16 youth and professional adult basketball players. To support their long-term sport development, it is recommended that youth basketball players focus their attention with longer final fixation before releasing the ball to improve their shot.